Acidified water extraction increases carpaine yield from Carica papaya L. Leaf - Sim, Tze Tak; Nor Hisam, Zamakshshari; Mohamad Fhaizal, Mohamad Bukhori; Eswaran, Madiahlagan; Rafeah, Wahi; Lawrence, Anchah (Malaysian Society for Molecular Biology and Biotechnology, 2024)
Abstract Aims This study presents a protocol for the Pharmacy Integrated Community Care (PICC) program, meticulously designed to enhance Hemoglobin A1c (HbA1c) levels and augment knowledge about diabetes mellitus (DM) among individuals diagnosed with Type 2 Diabetes Mellitus (T2DM) in the Sarawak State of Malaysia. Methods From 1 May to December 31, 2023, a prospective, multicenter, parallel-design randomised controlled trial will be conducted with two groups, each consisting of 47 participants. The intervention group will receive a structured, four-session group-based program guided by experienced pharmacists, focusing on medication adherence and diabetes management. The control group will follow the standard Diabetes Mellitus Adherence Clinic program. The primary outcomes of this study encompass enhancements in knowledge regarding diabetes medication management and adherence, followed by subsequent changes in HbA1c levels. Conclusions The successful implementation of the PICC program holds promise for enhancing health outcomes in the T2DM population, potentially leading to more effective diabetes management initiatives and better health practices in the community. Trial registration clinicaltrials.gov identifier NCT05106231.